Analisis Budaya Organisasi Dalam Kualitas Manajemen Pendidikan Dalam Lingkup Lembaga Pendidikan - Riyan Adhitya Pratama; Naufal Aldrian Kurniawan; Muhammad Daffa Adi Prayogo; Aryo Anargya Hakim Putra (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This research was conducted to determine how much organizational culture of an educational organization. One of the factors supporting the success of an Educational Management is the existence of a balanced organizational culture that is applied in an educational institution itself. Quality educational institutions must be able to determine the balance influences the quality of an educational management within the scope of educational institutions. The dynamics of the success of Education Management in Indonesia determine the quality in community satisfaction as consumers. Educational Institutions must be built from an Organizational Culture that provides strength in the process of carrying out Education Management. Data collection methods used in this study using quantitative methods. The data collection technique used in this study was carried out by developing relevant data and theories from various journals, theses, articles and theses. The research results are obtained if there are still many educational institutions in Indonesia that still do not implement organizational culture which results in a lack of educational management that has an impact on the community itself.